Labor transfer, market development, and the outsourcing of forestry production by farmers: a case study in Fujian, China - Wen, Yaping; Feng, Liangming; Liu, Weiping (Frontiers in Sustainable Food Systems, 2023)
The outsourcing of forestry production is an important form in the development of forestry specialization and is the compromise result of economic incentives, factor optimization and risk diversification for farmers. It can facilitate the collaboration between internal and external resources to improve the efficiency of resource allocation and promote the combination of small farmers and the high-quality development of modern forestry. In this research, we have analyzed the extrusion effect, the substitution effect, and the income effect of labor transfer on the outsourcing of forestry production by farmers based on the theory of farmers' behavior. In addition, we have constructed an influence mechanism for the development of the outsourcing services market according to the theory of division of labor. Moreover, we analyzed research data from farmers in Fujian Province using a probit model to determine the effect of labor transfer and market development on the outsourcing of forestry production by farmers. The conclusions showed that several factors have a significant impact on the outsourcing of forestry production. These factors include labor transfer, market development, income level in the village, smaller machinery numbers, amount of forestry subsidies, extent of forest road construction to meet production demands, and degree of forest land fragmentation. We have discussed topics of the distribution of labor value, market structure cultivation, and forestry costs on conclusion. Finally, we propose increasing farmers' income through labor transfer, fostering the market for outsourcing services in forestry production, and promoting the new classification of forestry.